Crisis Communication by the Indonesian Government in Handling Covid-19 - Nurfadhilah, Alfi; Rahmanto, Andre; Muhammad, Albert (KnE Social Sciences, 2022)
This study aimed to explore the crisis communication strategy of DKI Jakarta and the Banten Provincial Government in handling Covid-19 through the @dkijakarta and @pemprov.banten Instagram accounts. According to SCCT, there are two functions of crisis communication, namely to ensure public safety and manage the reputation of the organization. This research was conducted using a qualitative content analysis method, where the researcher examined the content of the Instagram accounts @dkijakarta and @pemprov.banten in the period of June 2021. The results showed that DKI Jakarta and the Banten Regional Government used their Instagram accounts to disseminate instructions on handling Covid-19 and at the same time to publish their performance in overcoming the crisis. However, more posts contained performance details than instructions. Hence, the West Java Regional Government prioritized the image of their institution, rather than managing the public’s safety. In addition, the researchers found that in providing instructive messages, @dkijakarta and @pemprov.banten used a persuasive strategy, which combined logical and emotional aspects to create behavior changes. Keywords: crisis communication, government communication, social media